Astronomical constraints on the duration of the Early Jurassic Pliensbachian Stage and global climatic fluctuations - Ruhl, Micha; Hesselbo, Stephen P.; Hinnov, Linda; Jenkyns, Hugh C.; Xu, Weimu; Riding, James B.; Storm, Marisa S.; Minisini, Daniel; Ullmann, Clemens V.; Leng, Melanie J. (Elsevier, 2016)
The Early Jurassic was marked by multiple periods of major global climatic and palaeoceanographic change, biotic turnover and perturbed global geochemical cycles, commonly linked to large igneous province volcanism. This epoch was also characterised by the initial break-up of the super-continent Pangaea and the opening and formation of shallow-marine basins and ocean gateways, the timing of which are poorly constrained. Here, we show that the Pliensbachian Stage and the Sinemurian–Pliensbachian global carbon-cycle perturbation (marked by a negative shift in δ13Cδ13C of 2–4‰2–4‰), have respective durations of ∼8.7 and ∼2 Myr. We astronomically tune the floating Pliensbachian time scale to the 405 Kyr eccentricity solution (La2010d), and propose a revised Early Jurassic time scale with a significantly shortened Sinemurian Stage duration of 6.9±0.4 Myr6.9±0.4 Myr. When calibrated against the new time scale, the existing Pliensbachian seawater 87Sr/86Sr record shows relatively stable values during the first ∼2 Myr of the Pliensbachian, superimposed on the long-term Early Jurassic decline in 87Sr/86Sr. This plateau in 87Sr/86Sr values coincides with the Sinemurian–Pliensbachian boundary carbon-cycle perturbation. It is possibly linked to a late phase of Central Atlantic Magmatic Province (CAMP) volcanism that induced enhanced global weathering of continental crustal materials, leading to an elevated radiogenic strontium flux to the global ocean.